KUR'AN ILE MEYDAN OKUMA - SEDEEQ, MOHAMEDSEDIQ JAAFAR (Fırat Üniveristesi, 2019)
Kur'anı Kerim'in meydan okuması, onun bir benzerini getirme konusunda inkarcıların acziyetini ortaya koymayı ve Hz. Muhammed'in peygamberliğini isbat etmeyi amaçlamaktadır. Kur'ân-ı Kerim beşer kelamı değil Allah'ın sözüdür. İnsanları şirke ve putlara ibadet etmeye çağıran bir topluluk bu dine itiraz etmiştir. İslam, bu bozuk akideyi düzeltmek ve insanlara hem dünya hem de ahiret mutluluğunun yolunu göstermek için yüce bir doktrin getirmiştir. İslam düşmanları günümüzde de insanları bu dinden uzaklaştırmak için Kur'ân hakkında yersiz inanç ve şüpheleri yaymaya devam etmektedirler. Kur'ân'ın meydan okuması bu şüpheleri ortadan kaldırmanın en kolay yoludur. Bu çalışma, Kur'ân'ın meydan okuması ve ona dair tartışmalara ilişkin bazı konuları analitik bir metotla araştırmaktadır. Bu konulardan bazıları, meydan okumanın aşamaları, meydan okumanın ulaştığı derece, sarfe teorisi, Kur'ân'da bahsi geçen gaybi haberler ve meydan okumanın hususi yönüdür. Çalışmanın sonunda araştırmanın en önemli sonuçları zikredilmiştir.

The challenge of the Holy Quran is asking for the same of the Holy Quran to the purpose of denying the deniers to prove them the prophecy of our Prophet Muhammad, (peace be upon him). Also to prove that the holy Quran is the word of Allah and it's not the words of humans. Some people stand against the religions who were calling to polytheism and worship idols. Islam came with its lofty roles to reform these corrupt doctrines and guide people to what is good for this world and the hereafter. The enemies of Islam are still spreading suspicions and illusions about the holy Quran to keep people away from this religion. The challenge of the Holy Quran was the easiest way to push these suspicions. This research looks at some of the issues which related to the subject of the challenge and discussed by studying and analyzing them. Also included the stages of the challenge and the extent to which the challenge occurred and the theory of Al-Surfa, metaphysical news contained in the Holy Quran especially challenge. Then concluded the most important conclusions derived from this research.
The Challenging with Qur'an
Keywords: Din